2000
DOI: 10.1295/polymj.32.91
|View full text |Cite
|
Sign up to set email alerts
|

Microemulsion Polymerization of Butyl Acrylate. Effect of Radical Scavenger and Formation of Primary Radicals

Abstract: :Microemulsion polymerizations of butyl acrylate initiated by dibenzoyl peroxide in the presence of a radical scavenger (RS)(stable radicals: an oil soluble RS: 4-stearoyloxy-2,2,6,6-tetramethyl piperidine-1-oxyl (STPO) and water soluble RS: 4-hydroxy-2,2,6,6-tetramethyl piperidine-1-oxyl (HTPO)}were investigated. STPO and HTPO decreased the rate of polymerization and the decrease was more pronounced with STPO. Inorganic salts and organic additives decreased the rate of polymerization. The shift of the maximum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 36 publications
1
2
0
Order By: Relevance
“…This small particle size of PMMA may be attributed to the retardation in particle growth. Similar results of smaller particle size and retardation in particle growth were reported by Capek et al 25 in the microemulsion polymerization of butyl acrylate in presence of radical scavenger. Thus, complex catalyzed emulsifier-free emulsion polymerization can hopefully be utilized to prepare nanoscale latex particles.…”
Section: Resultssupporting
confidence: 89%
“…This small particle size of PMMA may be attributed to the retardation in particle growth. Similar results of smaller particle size and retardation in particle growth were reported by Capek et al 25 in the microemulsion polymerization of butyl acrylate in presence of radical scavenger. Thus, complex catalyzed emulsifier-free emulsion polymerization can hopefully be utilized to prepare nanoscale latex particles.…”
Section: Resultssupporting
confidence: 89%
“…From the Arrhenius plot of log R P versus 1/ T (Fig. 4), the overall activation energy, E a , was found to be 39.26 kJ/mol and, taking E P = 16.2 kJ/mol, E t = 15.5 kJ/mol reported for AN,28 the activation energy for initiator decomposition was found to be 61.62 kJ/mol by using the formula and the number of micelles, 0.122 × 10 18 against the theoretical values27 of 10 18 , characteristics of emulsifier‐free emulsion polymerization. Figure 5 shows the relationship between R p with the reciprocal of DP of PAN at different initiator concentrations at 50°C.…”
Section: Resultsmentioning
confidence: 88%
“…From the experimental evidence, it is observed that particle size increases with increase in concentration of complex at decreasing temperature (Table II). Hence it may be suggested that the polymerization was stabilized by the presence of the complex with reduction of the particle size into the nano range 27…”
Section: Resultsmentioning
confidence: 99%